1997
DOI: 10.1111/j.1365-2125.1997.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic tramadol has minimal effect on gastrointestinal motor function

Abstract: Aims The analgesic tramadol, an opioid agonist and monoaminergic reuptake blocker, has been assumed to interfere less with gastrointestinal motor function than other opioid analgesics, but this has not been specifically investigated. In this study we examined the effect of tramadol on variables of gastrointestinal motor fimction. Methods Ten healthy volunteers participated in a two-arm, placebo-controlled, double-blind, randomized, cross-over study comparing tramadol 50 mg and placebo solutions given four time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…In one study tramadol was found to slow colonic transit time to a small extent in healthy volunteers, but had no effect on upper gastrointestinal motility [21]. Another study found tramadol to have a measurable but smaller inhibitory effect on gastric emptying than morphine and codeine [22].…”
Section: Discussionmentioning
confidence: 99%
“…In one study tramadol was found to slow colonic transit time to a small extent in healthy volunteers, but had no effect on upper gastrointestinal motility [21]. Another study found tramadol to have a measurable but smaller inhibitory effect on gastric emptying than morphine and codeine [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol is considered to have a low abuse potential, and unlike opiates, is not a controlled substance (Desmeules, 2000). In other species, tramadol has little effect on GI motility, no clinically relevant cardiovascular or respiratory effects, and lacks pharmacodynamic tolerance (Wilder Smith & Bettiga, 1997; Scott & Perry, 2000; Klotz, 2003; Grond & Sablotzki, 2004). Therefore, tramadol is a first‐choice drug for moderate to severe pain, especially in patients with compromised cardiovascular and pulmonary function (Scott & Perry, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although research suggests that tramadol exhibits a measurable but smaller effect on gastrointestinal motility than that of conventional opioids such as codeine and morphine, care should be taken while administering higher doses. 14,23,24…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse events associated with the use of tramadol are dizziness, nausea, vomiting, headache, constipation, and somnolence . Tramadol has been reported as less likely to lead to respiratory depression and has less effect on the gastrointestinal motor function than pure opioid agonists at equianalgesic doses …”
mentioning
confidence: 99%
See 1 more Smart Citation